PENGARUH GAME ONLINE TERHADAP PRESTASI BELAJAR REMAJA KOMPLEK KORPRI KABUPATEN KUBURAYA (STUDI KASUS: MOBILE LEGENDS) - Endah Pangesti, Witriana; Ade Safitri, Rizky; Nur Azizah, Qudziah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Current technological developments especially those related to smart computer technology are growing rapidly. Until the cellphone was originally used to meet communication needs only, now mobile phones can be used to do many things, such as used to find any information that is in the world very easily, playing online games anywhere and so on. Mobile Legend game is very popular not only by teenage boys, but there are also many teenage girls who like to play online games. According to Fendy, now the "Mobile Legends application: I have downloaded 35 million times and there are 8 million daily active users in Indonesia". The Korpri complex of Kubu Raya West Kalimantan is an object chosen by the writer to be an object of research that focuses on young men and women aged 12 to 24 years. This research was conducted using simple linear regression method and the data was processed using SPSS version 24 software. The results of this study note that a significant value of 0.686 is greater than> 0.05 probability, so it can be concluded that there is no influence of playing mobile legends (X ) towards youth learning achievement (Y).